Edgar Allan Poe and Juan Eduardo Cirlot: symbol and negativity - Fernandez Castillo, Jose Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This article examines the reception of the works of Edgar Allan Poe (1809-1849) by the Spanish poet Juan Eduardo Cirlot (1916-1973) and, especially of Poe’s poem «Ulalume», lauded by Cirlot as one of the most important texts of modern poetry. To interpret the Bronwyn poetry series from the theory of the symbol implicit in «Ulalume» allows us to go beyond the discussion of literary debts to consider the notion of symbolism in Cirlot's work in relation to the legacy of Romanticism. Cirlot emphasises the negative component of symbolism that characterises Poe’s «Ulalume» (distance between the symbolizing present and the symbolized absent) and places it at the centre of his poetic practice. The Spanish author outlines, in this way, a tragic conception of symbolism, divided between nihilism and a particular form of mysticism without ultimate fusion.
Keywords: Edgar Allan Poe; Juan Eduardo Cirlot; poetic symbolism; comparative literature; Postromanticism